Shakespeare and Youth Culture - Hulbert, Jennifer. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
This book explores the appropriation of Shakespeare by youth culture and the expropriation of youth culture in the manufacture and marketing of 'Shakespeare'. Considering the reduction, translation and referencing of the plays and the man, the volume examines the confluence between Shakepop and rock, rap, graphic novels, teen films and pop psychology.